Remote sensing land-cover change in Port Elizabeth during South Africa's democratic transition - John Odindi; Paidamwoyo Mhangara; Vincent Kakembo (South African Journal of Science)
Urban population increase has caused significant urban landscape transformation globally. Before 1994, South Africa's highly regulated urban growth was shaped by the restrictive Prevention of Illegal Squatters Act of 1951. After the abolishment of the act in the 1980s, the period of transition to democracy in the 1990s was characterised by an unprecedented urban population influx that caused a myriad of socio-economic and environmental challenges. These challenges have consequently compounded the need to monitor urban growth for the planning and optimisation of urban spaces. The limitations of traditional mapping methods, such as surveying and photogrammetry, in urban mapping are well documented. In the recent past, satellite remote sensing has emerged as one of the most viable urban mapping tools. Using post-classification comparisons, we sought to monitor major land use and land cover (LULC) changes in the city of Port Elizabeth during South Africa's democratic transition (1990-2000). Images for 1990, 1995 and 2000 were acquired, geo-rectified and atmospherically corrected. An iterative self-organising data analysis (ISODATA) was then used to generate existing LULCs. Classes generated using ISODATA were then amalgamated to the city's major LULCs and resultant classes were validated using aerial photographs and field visits. Results showed that 'Built-up' and 'Bare surface' LULC classes had the highest increase and decrease, respectively. There was no change in the 'Beach or dune' LULC, whereas 'Green vegetation' and 'Water' classes had minimal changes. This study illustrates the efficacy of remote sensing in monitoring urban change and the potential of remote sensing to aid decision-making in rapidly changing urban landscapes.